HISBAH: MODEL KONSELING ISLAM KLASIK DALAM IMPLEMENTASI DI SEKOLAH UNTUK MENGATASI KRISIS SPIRITUAL - Tri Putri Amelia S; Marsal Yunas Muliadi Hasibuan; Dasril Dasril (Realita : Jurnal Bimbingan dan Konseling, 2023)
This study aims to explore the implementation of the classical Islamic counseling model in education. The classical Islamic counseling model is also known as hisbah which was first implemented during the time of Khalifah Umar bin Khattab. Hisbah is seen as important and relevant to be applied in modern era school settings, especially for alleviating the spiritual crisis in adolescents as an implication of globalization. The research method uses descriptive qualitative methods and uses data collection techniques in the form of observation and in-depth interviews. The results of this study indicate that the implementation of hisbah in school settings has been carried out in the form of: 1) giving advice, 2) individual guidance, 3) individual counseling, and 4) mass counseling. The problem being addressed is the spiritual crisis caused by the various impacts of globalization today. Based on the results of the study, it can be concluded that hisbah has been implemented properly and is in accordance with current developments due to the various values, principles and aspects that underlie the process of integrated guidance and counseling services in schools to alleviate the spiritual crisis which is an achievement or target in counseling in schools.